The Dialogical Relationship as a Prerequisite for Identifying a Human Person - Glinkowski, Witold Piotr (Sensus Historiae, 2020)
The main purpose of the article is to demonstrate that even if a man’s personal identification is a commonly available process, which can be spontaneously and blindly triggered by each human being, it is still accompanied by certain assumptions, premises, and conditions that render it feasible. The process of personal identification - which refers to the subject him/herself and other people - focuses on a human person as an empirically elusive object. Even though man is recognisable by references to their genotype, phenotype, morphological features, cultural competences, etc., it remains difficult to determine the criteria and premises that allow us to decide whether an individual that we are facing is a human person. The concept of human person, introduced into the glossary of philosophical and philosophically anthropological terms during early medieval Trinity disputes, is a notion as non-negligible as troublesome. It seems that the modern philosophy of dialogue is the very first realm in which the issue of identifying the human person is provided with an explanation that overcomes and legitimately ignores previously insurmountable dilemmas. For dialogists, the fact that somebody is a human person comes down to being a You - a partner in a dialogical relationship. The process of identifying someone as a human person - oneself or somebody else, as these two aspects are inseparable - is conducted when we enter and remain in dialogical relationships. I face a human person whenever I open myself to a possible partner of a relationship as if encountering such a person, i.e. recognising him/her as a human person. And yet, the prerequisite for identifying someone as a human person consists in undertaking an existential action whose properties are about to ascertain me of my being a human person myself. This reminds of the biblical story (Luke 10: 29-37), whose protagonist recognises a robbed man as his neighbour, but in order to do so, he himself has to show first that he is a neighbour too, whose hero recognizes the other as a neighbour only after bearing himself witness of being a neighbour.